Abandono familiar y su incidencia en la salud mental de un adulto mayor de 67 años en la Parroquia La Esmeralda del cantón Montalvo - Ortega Coello, Patricio Enrique (2023)
Family abandonment is an issue that has been very little taken into account in society, old age is a stage that has to be very important as far as the human being is concerned. That is why in this case study we will address this problem in an older adult of 67 years in the parish La Esmeralda of Montalvo canton, where we will investigate bibliographical references of other authors who have studied family abandonment, as well as mental health and whether there is any impact on it because of family abandonment. In this case study data have been obtained with the mixed approach method, applying techniques such as observation, interview, observation, as well as the application of psychometric tests which provide relevant data on the cognitive and social status of the case to be studied.